Analisis Konteks Historis Film Sejarah Perang Banjar Sebagai Media Edutainment - Heri Susanto; Sariyatun Sariyatun; Djono Djono (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2022)
Apart from being an entertainment medium, movies with historical settings also have the potential for learning history, but not many history teachers have used film as a learning media. This research aims to analyze the feasibility of the Banjar War movie as a memory-based edutainment media. This is qualitative research, the research subjects being Banjar history experts and practitioners of history teaching. The design of this research is a case study related to the history of the Banjar war shown in the movie. Collecting data using interviews and questionnaires with respondents from Banjar history experts and the creators of the Banjar War film and analysis of film content. Instrument validation is carried out with internal validation and external validity. To ensure the quality of the instrument, it is carried out with credibility and transferability. The credibility of the data is done by triangulation of sources and triangulation of methods. In comparison, the data analysis using the Spradley model, namely, analysis of a domain, analysis of taxonomic, analysis of componential, and analysis of cultural theme. Results of this study show 1) the factual aspects show conformity with related Banjar historiographical works although there are some factual shortcomings, 2) the chronology of the film story is relevant to the historical setting, 3) the suitability of the periodization, as a whole shows the compatibility between the artifact, mentifact, and contemporary sociofact components, 4) the edutainment aspect of this film meets the criteria to be used in history education. This research concludes that teachers can use the Banjar war film as an edutainment-based historical learning media by emphasizing an objective analysis approach to students.